Semi-immersive virtual reality environment / Marina Ismail - Ismail, Marina (2006)
This project is about to implement a prototype of Semi-immersive Virtual Reality Environment for Museum Sultan Alam Shah at gallery history. The QuickTime VR technology with image-based approach was used to develop the virtual walkthrough at the museum. MLC methodology used to monitor the whole process of development of this project. Museums are keen on presenting their collection in more appealing and exciting manner to attract visitors. Hence, to create the virtual reality environment for the scene we use virtual tour for the visitors or users to visit the museum virtually without physically present. We use an Image based approach to create the real environment with 360 degrees and objects with three dimensions. From the tour visitors are able to move forward, backward, upward and downward. Panorama can be fully interactive through the use of "hotspots" to link the user to other scene and object. The object or artifact can moved by hand that give the 3-dimensional feeling when viewing an object. Actually the interactive object is manipulating and viewing the object from each angle. Plug in Quick Time Player as the player platform for virtual walkthrough is used to start and explore the virtual environments.